Pubertal Timing and Tempo: Associations With Childhood Maltreatment. (31st March 2014) - Negriff, Sonya; Blankson, A. Nayena; Trickett, Penelope K.
<x xml:space="preserve">Abstract</x> This study examined pubertal timing and tempo in a sample of 445 adolescents (53% male), using both variable‐centered (latent growth curve) and person‐centered (latent class) approaches, to discern the pubertal development trajectories associated with the experience of maltreatment. Results from the variable‐centered analyses indicated a slower initial tempo that increased later for boys who had experienced neglect. The person‐centered results indicated three classes for boys that mainly differentiated tempo effects and two classes for girls primarily distinguishing timing differences. For girls, sexual abuse predicted membership in an earlier pubertal timing class. These findings enhance our knowledge of the variability in pubertal development as well as gender differences in maltreatment types that may alter pubertal timing and tempo.